Impact of Radiation Dose on Survival for Esophageal Squamous Cell Carcinoma Treated With Neoadjuvant Chemoradiotherapy - Yang, Yang; Xu, Xiaofang; Zhou, Xia; Bao, Wuan; Zhang, Danhong; Gu, Feiying; Du, Xianghui; Chen, Qixun; Qiu, Guoqin (Frontiers in Oncology, 2020)
Purpose: Radiation dose used in the neoadjuvant chemoradiotherapy (NCRT) for patients with locally advanced esophageal squamous cell carcinoma (ESCC) varies in different trials and clinical practice. Methods and Materials: Patients diagnosed with ESCC receiving NCRT followed by esophagectomy were retrospectively collected from February 2013 to December 2017. Lower dose (LD) radiotherapy was defined as ≤45Gy, and >45Gy was considered as higher dose (HD). Survival rates were calculated by the Kaplan–Meier method and compared with long-rank test. Multivariate Cox regression analyses were performed to identify variables associated with survival. Results: A total of 118 patients treated with NCRT were included in our analysis, 62 patients received LD radiotherapy, and 56 patients received HD radiotherapy. The median follow-up time was 24.3 months (0.67-65.3m). 2-year overall survival (OS) rates were 75.0% and 79.0% in HD and LD group respectively (P=0.360), and complete pathological remission (pCR) rates in two groups were 42.9% and 30.6%, respectively (P=0.17). The incidences of toxic effects including postoperative complications were not significantly different between two groups. Multivariate analysis showed that tumor T stage, M1a disease, smoking history and pCR rate were significantly associated with OS. Conclusions: In ESCC patients treated with NCRT followed by surgery, higher radiation dose was not significantly associated with a higher pCR rate and longer survival. Lower radiation dose might be a preferable time-dose fraction scheme. Our finding needs to be further validated by randomized trials.